2005
DOI: 10.1021/bi051288d
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Catalytic Amino Acids in the Human GTP Fucose Pyrophosphorylase Active Site

Abstract: GTP-l-fucose pyrophosphorylase(GFPP) catalyzes the reversible formation of the nucleotide-sugar GDP-beta-l-fucose from guanosine triphosphate and beta-l-fucose-1-phosphate. The enzyme functions primarily in the mammalian liver and kidney to salvage free fucose during the breakdown of glycoproteins and glycolipids. GFPP shares little primary sequence identity with other nucleotide-sugar metabolizing enzymes, and the three-dimensional structure of the protein is unknown. The enzyme does contain several sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 39 publications
(46 reference statements)
0
34
0
Order By: Relevance
“…[11] The ability of Flex-GTP to interact with secondary amino acids within the binding site led to more favorable binding interactions, thereby increasing the affinity in GFPP when compared to GTP. [11,12] In addition to our findings, groups such as Hudson et al have pursued a series of analogues using click chemistry in which they have found interesting fluorescent properties. [13] It is important to note that, to date, no toxicity has been observed with any of the members of this interesting class of nucleosides.…”
Section: Introductionmentioning
confidence: 67%
“…[11] The ability of Flex-GTP to interact with secondary amino acids within the binding site led to more favorable binding interactions, thereby increasing the affinity in GFPP when compared to GTP. [11,12] In addition to our findings, groups such as Hudson et al have pursued a series of analogues using click chemistry in which they have found interesting fluorescent properties. [13] It is important to note that, to date, no toxicity has been observed with any of the members of this interesting class of nucleosides.…”
Section: Introductionmentioning
confidence: 67%
“…4,5 In addition to SAHase inhibition, it was also found that the triphosphate analogue of Flex-G was a significantly better substrate for GTP fucose pyrophosphorylase (GFPP) than the natural substrate GTP, and was able to retain full activity when key amino acid residues required for GTP recognition were mutated. 6,7 Notably, GTP was rendered completely inactive.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] Similar to Tenofovir 25 and Etravirine, [26][27][28] both FDA-approved HIV-1-RT inhibitors, our compounds' inherent flexibility allows them to overcome resistance mechanisms related to point mutations. 29,30 The concepts of conformational flexibility and positional adaptability, or the ability to 'wiggle and jiggle' in a binding site when confronted with an active site mutation have now been shown [26][27][28] to be critical for avoiding resistance mechanisms for non-nucleoside HIV-1-RT inhibitors, thus provide additional impetus for our approach.…”
Section: Introductionmentioning
confidence: 99%